A green-Ampt model considering unsaturated zone and pore air pressure - Youliang Peng; Liangjun Fei; Fangyuan Shen; Runqiao Zheng; Qian Wang; Qianwen Fan (Geoderma)
The relationship between infiltration time and the depth of the wetting front can be solved using Darcy’s law. According to this, the infiltration rate is equal to the derivative of the infiltration amount regarding time. However, the traditional Green-Ampt model considers the infiltration amount on the basis of the complete saturation of the wetting regions while ignoring the effect of pore gas pressure. This limits the calculation accuracy of the relationship between infiltration time and wetting front depth. As a response to this problem, this paper analyses the effects of soil bulk density and surface water depth on soil moisture content and pore air pressure at varying depths during water infiltration. It then constructs models for the unsaturated regions and additional pore gas pressure as a means of adjusting the cumulative infiltration volume and infiltration time separately. The results demonstrate that as the bulk density of the soil increased, the infiltration rate decreased while the time required for the wetting front to reach the measurement point increased. As the surface water depth increased, the infiltration rate also increased. During the water infiltration process, the change in pore gas pressure was a continuous state, which can be divided into two phases: rapid change and slow change. The maximum and stable pore air pressure were positively correlated with the surface water depth and soil bulk density during the infiltration process. In comparison to the measured values, the accuracy of the infiltration amount that was calculated by the combination model was the highest, followed by the ellipse model and the original model was the worst. Of the three Green-Ampt models, the infiltration time that was calculated using the Green-Ampt model that considered the pore pressure and unsaturated regions was closer to the measured values. This was followed by the Green-Ampt model that considered the unsaturated regions and the traditional Green-Ampt model was the worst. In addition, the Green-Ampt correction model that considered soil bulk density and surface water depth rather than stable pore air pressure did not affect the accuracy of the experiment. The research results can provide theoretical reference for improving the application of the Green-Ampt model.